Institutions, regulation and governance of the internet: A European perspective on traffic, uses and business practices in the digital economy - Jonathan Liebenau; Silvia Elaluf-Calderwood (International Telecommunications Society (ITS), 2013)
The business of the internet behaves distinctly in Europe from elsewhere, belying clichés about the digital economy being global, flat and neutral. Those differences are mainly associated with distinctive business practices and they are manifest in the architecture and dynamic features of digital traffic, the business models that are built upon that system, and the governance that applies. In this paper we describe these differences and show how the structure of competition, regulators and other governance mechanisms define n economic model for Euope distinct from that of the US and elsewhere. We base our analysis on evidence about the type, volume and routing of digital traffic. We show that in addition to the vast differential in revenue accrued through different types of traffic (e.g. SMS, voice, streaming videos, software download, etc.) there are great differences in the profitability that different stakeholders in the digital economy can command. These differences stem from different strategic uses off the internet architecture, different market structures, and crucially differences in the institutions and governance of the European internet.
Keywords: 330